Relationship between the preference and perceived restorative potential of urban landscapes. - Abkar, Mahdieh; Mohd Shariff, Mustafa Kamal; Maulan, Suhardi; Mariapan, Manohar; Davoodi, Seyed Rasoul (American Society for Horticultural Science, 2011)
This study presents the relationship between "perceived restorative potential" (PRP) and "preference" for an environment with respect to their relationship with the restorative components outlined by attention restoration theory (ART) in two categories: urban built landscape (UBL) and urban natural landscape (UNL). In this experimental study, 120 participants from University Putra Malaysia (Serdang, Malaysia) rated four restorative components, the PRP and "preference" of 24 color slides depicting UBL and UNL scenes. The results showed that "preference" and PRP was moderately correlated in UNL and UBL. "Compatibility" was found to be the most influential variable among all the restorative components in explaining PRP and "preference" in both UNL and UBL. However, "fascination" appeared to be the second most significant predictor of "preference" in UNL, whereas "being away" was the second most significant predictor of PRP in UNL. Furthermore, "coherence" predicted "preference" but it did not predict PRP in UNL. "Being away" and "coherence" were distinct components of PRP and "preference" and of UNL and UBL.